Orofacial injuries reported by junior and senior basketball players - Leisc, N.; Seifert, D.; Jerolimov, V. (Collegium Antropologicum, 2011)
The increased popularity of sports, apart from being beneficial to health, also results in a larger number of injuries, a part of which are also injuries to the stomatognatic system. Acording to the data from literature orofacial injuries in basketball are frequent, but relatively minor. The World Dental Federation places basketball into the category of medium-risk sports for the occurrence of injuries to the stomatognatic system. The purpose of this investigation was to determine incidence, type and severity of orofacial injuries during basketball and the frequent of the mouthguard use in a selected sample of basketball players from the City of Zagreb and the Zagreb County. The sample consists of 195 athletes who actively participate in basketball, 61 junior and 134 senior players. A total of 2 615 injuries to the stomatognatic system were documented in this research, 529 (20.2%) of those refer to juniors and 2 086 (79.8%) to seniors. The most common injuries are lacerations and contusions of soft tissue 84.4% (21.5% juniors and 78.5% seniors), followed by temporomandibular joint injuries and oral muscles stiffness 13.4% (14.9% juniors and 85.1% seniors) and 2.2% dental injuries (3.5% juniors and 96.5% seniors). Only 6.7% of players (13 players - 2 juniors and 11 seniors) have tried to wear a mouthguard, while only one 1% of them (2 players - one junior and one senior) frequently used it. Total number of injuries shows that sports injuries are common during basketball. Average number of almost 4 injuries per player is relatively high. Dental injuries and temporomandibular joint injuries and oral muscles stiffness are relatively rare, only 16%. Lacerations and contusions of soft tissues represent 84% of all injuries and that minor injuries do not require professional care.